Impact of rainfall variability and extremes on crop intensification and diversification in the coastal region of Bangladesh - Islam, H. M. Touhidul; Ahmed, Sharif; Kamruzzaman, Mohammad; Kumar, Virender; Bhandari, Humnath (Elsevier, 2025)
The coastal regions of Bangladesh are highly vulnerable to climate change. Crop intensification and diversification in these areas are lower than in other parts of the country due to multiple environmental stresses, particularly higher rainfall variability and extremes with other stresses. The current study investigates the impact of rainfall variability and extremes on crop intensification and diversification in the coastal region of Bangladesh. Based on the historical climate data (1980-2020), this study examines the onset (ON) and withdrawal (WD) of monsoon precipitation by forward and backward accumulation techniques and the probability of dry and wet spells utilizing the Markov Chain (MC) probability model. The average ON and WD of monsoon precipitation were found at the 21st-22nd and 43rd-44th standard meteorological weeks (SMWs), respectively, for all the stations. Extreme rainfall events have increased in recent periods (2001-2020) compared to earlier periods (1981-2000) in the rainfall months (Jun-Oct), potentially contributing to the recurrent flash floods and waterlogging. The probabilities of dry spells were more frequent in early (1st-17th SMWs) and late (43rd-52nd SMWs) periods, while wet weeks (18th-42nd SMWs) had a 40-100 % chance of precipitation. We also analyzed the effect of rainfall variability on aus (pre-monsoon rice) production, which has great potential in this area. Additionally, we assessed the frequency and return periods of extreme rainfall events during the dry months (Nov-Apr) to evaluate the risks and opportunities for rabi/non-rice crop cultivation. We found that higher return periods of extreme events might delay the sowing of rabi crops and have adverse effects, particularly during their maturity phases. This study emphasizes the optimized sowing windows and climate-resilient cropping systems to support sustainable crop intensification and diversification in coastal Bangladesh.